Analytical Detection Capabilities of Immunoassay‐Based Antiphospholipid Antibody Tests: Do They Matter?. Issue 8 (31st October 2013) - Lakos, Gabriella; Gurwitz, David
Abstract <table-wrap position="anchor" orientation="portrait"> <x xml:space="preserve">Table </x> Clinical Development Phases I‐III Regulatory, Quality, Manufacturing </table-wrap> Antiphospholipid syndrome is one of the most frequent autoimmune diseases, with approximately 1% prevalence in the general population. The syndrome is under‐recognized and underdiagnosed, and can have devastating consequences if untreated, mainly because of recurrent thrombosis. Both diagnosis and management remains challenging, but important progress has been made in the last couple of years in the detection and measurement of antiphospholipid antibodies, the hallmarks of antiphospholipid syndrome, and also in the management and treatment of the disorder. The concepts of antiphospholipid antibody profiling and risk stratification of patients have been emerging at the same time when new therapeutic approaches have become available, and new technologies are being developed or adapted to antiphospholipid antibody measurements. These methodological improvements not only support but also drive the progress that has been improving the outcome for patients with antiphospholipid syndrome.